The Influence of Service Failure, Service Recovery, and Customer Forgiveness on Customer Loyalty - Griselda Ananda; Innocentius Bernarto (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Dental clinic services are vulnerable to service failures that can reduce patient trust and loyalty. This study analyzes the effect of service failure, service recovery, and customer forgiveness on revisit intention at dental clinics. The study used a quantitative approach with a survey method of 235 respondents who had used dental clinic services. Data analysis was conducted using Partial Least Square–Structural Equation Modeling (PLS-SEM) through SmartPLS to test the measurement and structural models, including direct and indirect effects. The results show that service failure has a negative and significant effect on service recovery, customer forgiveness, and revisit intention. Conversely, service recovery and customer forgiveness have a positive and significant effect on revisit intention. Mediation analysis shows that service recovery and customer forgiveness significantly mediate the relationship between service failure and revisit intention. The research model has good predictive ability based on the R-square, Q-square, and model fit index values. These findings emphasize the importance of minimizing service failures and strengthening patient recovery and relationship management strategies to increase loyalty and revisit intentions at dental clinics.